Characterization of right ventricular remodeling and failure in a chronic pulmonary hypertension model - Aguero, Jaume (American Physiological Society, 2014)
In pulmonary hypertension (PH), right ventricular (RV) dysfunction and failure is the main determinant of a poor prognosis. We aimed to characterize RV structural and functional differences during adaptive RV remodeling and progression to RV failure in a large animal model of chronic PH. Postcapillary PH was created surgically in swine (n = 21). After an 8- to 14-wk follow-up, two groups were identified based on the development of overt heart failure (HF): PH-NF (nonfailing, n = 12) and PH-HF (n = 8). In both groups, invasive hemodynamics, pressure-volume relationships, and echocardiography confirmed a significant increase in pulmonary pressures and vascular resistance consistent with PH. Histological analysis also demonstrated distal pulmonary arterial (PA) remodeling in both groups. Diastolic dysfunction, defined by a steeper RV end-diastolic pressure-volume relationship and longitudinal strain, was found in the absence of HF as an early marker of RV remodeling. RV contractility was increased in both groups, and RV-PA coupling was preserved in PH-NF animals but impaired in the PH-HF group. RV hypertrophy was present in PH-HF, although there was evidence of increased RV fibrosis in both PH groups. In the PH-HF group, RV sarcoplasmic reticulum Ca(2+)-ATPase2a expression was decreased, and endoplasmic reticulum stress was increased. Aldosterone levels were also elevated in PH-HF. Thus, in the swine pulmonary vein banding model of chronic postcapillary PH, RV remodeling occurs at the structural, histological, and molecular level. Diastolic dysfunction and fibrosis are present in adaptive RV remodeling, whereas the onset of RV failure is associated with RV-PA uncoupling, defective calcium handling, and hyperaldosteronism.